Legislation to House Numbering in Austria from 1770 to Today - Christoph Schmetterer (Journal on European History of Law)
This article explores the legal history of house numbering in Austria from the second half of the eighteenth century to the present. Prior to 1930, federal authorities were responsible for the legal regulation of house numbering in Austrian cities and towns, yet subsequently individual states began to pass their own house numbering laws. However, both federal and state laws had to be implemented by the municipalities. The current study therefore provides a historical overview of the rescaling of house numbering law in Austrian, focusing particularly on the case of Vienna.